EPITAXIAL FILMS OF ZINC SELENIDE ON POROUS SILICON - V. I. Levchenko; L. I. Postnova; E. L. Trukhanava; V. P. Bondarenko (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
ZnSe epitaxial films are grown on (111)- and (100)-oriented Si substrates with a porous buffer layer by the thermal evaporation of ZnSe compound. The crystal structure of the deposited films was controlled by X-ray diffraction. The morphology of the films was studied by high-resolution scanning electron microscopy. It was demonstrated the porous buffer layer provides improving the quality of the films compared with films deposited on the monolithic silicon.